TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION AT SENIOR HIGH SCHOOLS - Junita, Tarnia; Mukhrizal; Elfrida (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
Reading strategy is an important role in teaching reading comprehension to achieve the goals of reading. The teacher must choose a strategy that supports the development of students' skills in analyzing the content of the text. The objectives of this research were to investigate EFL teachers’ strategies in teaching reading comprehension and the most frequent one applied by them. The subjects of this research consisted of 30 EFL teachers. This research was a survey design that used a quantitative approach. The instrument was a questionnaire using Vacca and Vacca’s theory and it was administrated to the respondents through Google Forms. The data were analyzed quantitatively using the Microsoft Excel software. The results of the research showed that the EFL teachers applied five strategies in teaching reading comprehension at Senior High Schools in Bengkulu City, namely the SQ3R, Reciprocal Teaching, Think-Aloud, QARs, and Scaffolding strategies. The most frequent strategy applied by them was the SQ3R which was as always category while other strategies were as often category. In conclusion, EFL teachers have applied various strategies in teaching reading comprehension at Senior High Schools. This research recommended that EFL teachers to apply all strategies in teaching reading comprehension.